2005
DOI: 10.1084/jem.20050978
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclast differentiation independent of the TRANCE–RANK–TRAF6 axis

Abstract: Osteoclasts are derived from myeloid lineage cells, and their differentiation is supported by various osteotropic factors, including the tumor necrosis factor (TNF) family member TNF-related activation-induced cytokine (TRANCE). Genetic deletion of TRANCE or its receptor, receptor activator of nuclear factor κB (RANK), results in severely osteopetrotic mice with no osteoclasts in their bones. TNF receptor-associated factor (TRAF) 6 is a key signaling adaptor for RANK, and its deficiency leads to similar osteop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
254
3
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 342 publications
(281 citation statements)
references
References 26 publications
(41 reference statements)
8
254
3
7
Order By: Relevance
“…The disparity between in vitro and in vivo osteoclast formation is reminiscent of a similar disparity in osteoclast formation in vitro and in vivo in mice lacking either TRAF6 or Atp6v0d2 in which osteoclasts are present in vivo, although functionally defective [31] and do not form from precursors in vitro [32,33]). One possible explanation for these discrepancies is the presence of other factors in the in vivo microenvironment which can partially compensate the A 1 R, TRAF6 or Atp6v0d2 deficiency, such as TGF-β [32]. In this work, we further probed the signaling pathways by which adenosine/A 1 R activation mediates its effect on osteoclastogenesis.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The disparity between in vitro and in vivo osteoclast formation is reminiscent of a similar disparity in osteoclast formation in vitro and in vivo in mice lacking either TRAF6 or Atp6v0d2 in which osteoclasts are present in vivo, although functionally defective [31] and do not form from precursors in vitro [32,33]). One possible explanation for these discrepancies is the presence of other factors in the in vivo microenvironment which can partially compensate the A 1 R, TRAF6 or Atp6v0d2 deficiency, such as TGF-β [32]. In this work, we further probed the signaling pathways by which adenosine/A 1 R activation mediates its effect on osteoclastogenesis.…”
Section: Introductionmentioning
confidence: 96%
“…Recent studies in our laboratory have revealed a novel role for adenosine/A 1 receptor (A 1 R) in osteoclastogenesis: A 1 R activation is required for both osteoclast formation and function in vitro and only function in vivo, as demonstrated using pharmacologic inhibitors and mice lacking adenosine A 1 receptors [29,30]. The disparity between in vitro and in vivo osteoclast formation is reminiscent of a similar disparity in osteoclast formation in vitro and in vivo in mice lacking either TRAF6 or Atp6v0d2 in which osteoclasts are present in vivo, although functionally defective [31] and do not form from precursors in vitro [32,33]). One possible explanation for these discrepancies is the presence of other factors in the in vivo microenvironment which can partially compensate the A 1 R, TRAF6 or Atp6v0d2 deficiency, such as TGF-β [32].…”
Section: Introductionmentioning
confidence: 96%
“…Interestingly, the anti-TNF-␣ antibody has been shown to suppress bone damage in patients who had no clinical improvement in terms of pain and inflammation (19), suggesting that, under arthritic condition, TNF-␣ exerts an important direct action on bone, which is independent of its action on the immune system. Although there has been no in vivo evidence that TNF-␣ induces osteoclastogenesis in mice lacking RANKL signaling or that TNF-␣ rescues osteopetrosis in such mice (20)(21)(22), TNF-␣ clearly acts on osteoclast precursor cells and changes the responsiveness of the cells under certain conditions (13)(14)(15). However, the molecular mechanism underlying the enhanced osteoclastogenic potential of osteoclast precursor cells in the presence of TNF-␣ remains to be elucidated.…”
mentioning
confidence: 95%
“…TNF-is also a potent inducer of osteoclast formation itself, and can either directly increase osteoclast formation or enhance the effects of RANKL. 52,53 In addition, TNF-can block osteoblast differentiation from marrow stromal cells by decreasing the expression of critical osteoblast transcription factors, such as runt-related transcription factor 2 (Runx2), TAZ (transcriptional co-activator with PDZ-binding motif) and osterix, induce apoptosis of mature osteoblasts, and increase support of myeloma cells by induction of IL-6. 15,54 Macrophage inflammatory-1 ␣ .…”
Section: Factors Driving Osteoclast Formation and Activity In Mmbdmentioning
confidence: 99%